2016
DOI: 10.1165/rcmb.2016-0017ps
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Asthma in Obesity. Pleiotropic Aspects of Obesity Produce Distinct Asthma Phenotypes

Abstract: The majority of patients with severe or difficult-to-control asthma in the United States are obese. Epidemiological studies have clearly established that obese patients tend to have worse asthma control and increased hospitalizations and do not respond to standard controller therapy as well as lean patients with asthma. Less clear are the mechanistic underpinnings for the striking clinical differences between lean and obese patients with asthma. Because obesity is principally a disorder of metabolism and energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(99 citation statements)
references
References 85 publications
3
89
1
6
Order By: Relevance
“…Obesity and metabolic syndrome are associated with an increased risk of coincident asthma and may represent distinct asthma phenotypes (Brumpton et al, 2013; Camargo et al, 1999). Some have traditional Th2-high asthma, but others have an increasingly recognized Th2-low asthma that tends to be more common in women, later in onset, and difficult to treat (Dixon and Poynter, 2016). …”
Section: Obesity-related Asthmamentioning
confidence: 99%
“…Obesity and metabolic syndrome are associated with an increased risk of coincident asthma and may represent distinct asthma phenotypes (Brumpton et al, 2013; Camargo et al, 1999). Some have traditional Th2-high asthma, but others have an increasingly recognized Th2-low asthma that tends to be more common in women, later in onset, and difficult to treat (Dixon and Poynter, 2016). …”
Section: Obesity-related Asthmamentioning
confidence: 99%
“…In this work, we used whole blood gene expression profiling to characterize the biology of a form of asthma in people with obesity known as “asthma complicated by obesity” (i.e., cases in which asthma preceded the development of obesity). Among 514 subjects who were diagnosed with asthma as children, we identified three coexpression network modules jointly associated with adult obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with a significantly higher risk for developing asthma, worse asthma symptoms, poor asthma control, and greater resistance to standard asthma therapies . A recent review postulated at least three (likely four) endotypes of asthma in people with obesity , distinguished by the relative timings of each disease’s onset (onset during childhood versus adulthood) and by their underlying pathophysiologies (differing effects of obesity on airway structure, function, sensitivity, and/or inflammation). A more complete understanding of the complex molecular relationships between obesity and asthma would drive the development of specific and effective preventive and therapeutic strategies for this overlap syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Foremost, obesity contributes to asthma exacerbation in children in whom the disease is mostly allergic. However, the underlying mechanisms remain poorly understood . Mechanical effects linked to overweight and adipose tissue (AT) accumulation, as well as obesity‐associated inflammation, have been implicated.…”
Section: Obesity and Asthmamentioning
confidence: 99%
“…However, the underlying mechanisms remain poorly understood. 18,19 Mechanical effects linked to overweight and adipose tissue (AT) accumulation, as well as obesity-associated inflammation, have been implicated. For example, It has been shown that breathing at low lung volumes 20 as well as augmented airway wall thickness, 21 increases airway reactivity.…”
Section: Obesity and Asthmamentioning
confidence: 99%